Tailoring the microstructure and charge transport in conjugated polymers by alkyl side-chain engineering. Issue 2 (9th December 2015) - Fall, Sadiara; Biniek, Laure; Odarchenko, Yaroslav; Anokhin, Denis V.; de Tournadre, Grégoire; Lévêque, Patrick; Leclerc, Nicolas; Ivanov, Dimitri A.; Simonetti, Olivier; Giraudet, Louis; Heiser, Thomas
Abstract : Transport measurements with in-situ XRD reveal low alkyl side-chain densities to induce an ordered helicoidal conformation with large electronic energy disorder. Abstract : Charge transport in conjugated polymers is critical to most optoelectronic devices and depends strongly on the polymer structure and conformation in the solid state. Understanding the correlations between charge carrier mobility, energy disorder and molecular assembly is therefore essential to improve device performances. Alkyl side-chains contribute to intermolecular interactions and are key to controlling the polymer microstructure and electronic properties. Investigating a set of polymers with common conjugated units but different side-chain functionalization provides new insights into the complex structure–transport relationship. Here, field-effect transistors and space-charge-limited current devices are used together with in situ grazing-incidence wide-angle X-ray scattering to study charge transport and morphology in a series of donor–acceptor copolymers. Probing hole mobility as a function of carrier density and orientation permits us to assess energy disorder and hopping rate anisotropy, while X-ray diffraction allows us to link transport properties to the polymer microstructure. We show that branched side-chains enhance structural and energy disorder and lead to isotropic transport, whereas linear chains induce either a common lamellar structure or a more exceptional pseudo-hexagonal columnar phase with a helicoidal polymer conformation. The latter enhances out-of-plane mobility but increases energy disorder possibly due to larger interring torsion angles.